The Effect of Communication, Work Discipline and Work Life Balance on Employee Performance - Sigit Wicaksono, Angga; Hendri, M. Irfani; Daud, Ilzar; Rosnani, Titik (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the influence of communication, work discipline, and work-life balance on employee performance, with motivation as a mediating variable. The research data were collected through questionnaires distributed to 15 respondents. The results of the analysis show that communication has a positive and significant influence on employee motivation. In addition, work discipline is also proven to have a positive and significant influence on motivation. Likewise, work-life balance has a positive and significant impact on motivation. Furthermore, motivation has a positive and significant influence on employee performance. This study also found that communication, work discipline, and work-life balance each have a positive and significant influence on employee performance. Furthermore, motivation is proven to mediate the relationship between communication and employee performance. The same thing also happens in the relationship between work discipline and employee performance, as well as between work-life balance and employee performance, where motivation acts as a significant mediating variable. These findings indicate that improvements in communication, work discipline, and work-life balance can increase employee motivation, which in turn will have a positive impact on their performance in the workplace. Thus, efforts to improve these three variables are very important for management to pay attention to in order to improve overall employee performance.